Design and Testing of an Avian Hatchery Solar Energy Incubator for Smallholder Poultry Farmers from the Sudano-Sahelian Belt - Kisaalita, William S.; Bibens, Brian; Lane, Ed; Young, Patrick (Africa & Latin America, 2010)
The small scale (smallholder) poultry farmers of Burkina Faso face numerous challenges, one of which is lack of non-electric effective incubators with which to hatch chicken and guinea fowl eggs. The purpose of this paper was to evaluate the technical and economic feasibility of a cleaner alternative renewable energy powered incubator for a typical smallholder poultry farmer from the Sudano-Sahelian Belt with the central Burkina Faso as the model region. A solar powered system was designed based on the loading of two GQF Hova-BatorTM 2362 incubators. A BP Solar 3125U solar panel was chosen to accommodate the required loading based on the high solar energy in Burkina Faso. In addition, an ASC charge controller, UniRac solar mount, Exeltech inverter, and Concorde PVX 1040T deep cycle battery were chosen for the 80 watt load. Based on economic analysis, at full capacity (180 eggs), annual income was estimated at $4,127 with a net present value of $24,228 at 15 % interest. This included battery replacement every 5 years. Payback period was estimated at 5 months with benefits to cost ratio of 14.9. The Internal Rate of Return of 238% suggested the proposed incubator system to be an extremely attractive option for the smallholder poultry farmers in the Sudano-Sahelian Belt. The system was implemented in Burkina Faso and guinea fowl hatchabilities of 64.6 to 76.0 % were obtained.